Nowcasting As An Approach To Mitigate Economic Uncertainty In Syria - منصور, يُمن; إسماعيل , رولى; العكاري , خضر (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Economists suffer from incomplete knowledge of the current state of the economy, because to the late publication of economic indicators by the Central Bureau of Statistics, since the last census of economic indicators in Syria dates back to 2017, this leads to an economic uncertainty. The aim of this research is to use Nowcasting to obtain forecasts for the current and recent past (2018-2019) of the growth rates (investment, consumption, economic growth) to mitigate the economic uncertainty measured by the difference between the economists' expectations about Trend of economic indicators. The results indicate that the monthly inflation data (2007-2019) contain information that allows Now casting (2018-2019) of growth rates (investment - household consumption - economic growth) well. This allows the current track of indicators to be tracked and leads to the mitigation of economic uncertainty, the formulation of economic policies and effective decisions for the next phase in this light.